Estudio comparativo bibliográfico de tres adsorbentes naturales, utilizados para biorremediar aguas contaminadas con mercurio en la explotación aurífera. - Acuña Viteri, Carlos Andrés (2021)
In the present research, a comparative bibliographic study of three natural adsorbents was carried out to bioremediate wastewater contaminated with mercury in gold mining. According to (Andrade, 2018), the results show that in the physicochemical and biological characteristics of the waters from gold mining, the parameters exceed the maximum permissible limits of TULSMA, especially in mercury, exceeding from 0.01 ppm to 21.7 ppm. The natural adsorbents used in the analyzed studies are made of non-conventional materials formed by functional groups (hydroxyls, carboxyls, amines) and constituents such as lignin, cellulose, pectin that allow the affinity between the ligand and the metal, that is, the binding force giving itself the adsorption process. It was observed that Warao presents a higher percentage of adsorption of metal Hg2 + of 98%, the lowest percentage was for the combination of orange peel and ear of rice with 22% and moringa a value of 48%. It is establishing that in this analysis of the studies, the most optimal adsorbent of Hg2 + was the Warao biomass due to the alkaline pH, its longer contact time, and its composition as biomass that allowed the highest percentage of Hg2 + removal.